Lovo‐cel gene therapy for sickle cell disease: Treatment process evolution and outcomes in the initial groups of the HGB‐206 study. Issue 1 (10th October 2022) - Kanter, Julie; Thompson, Alexis A.; Pierciey, Francis J.; Hsieh, Matthew; Uchida, Naoya; Leboulch, Philippe; Schmidt, Manfred; Bonner, Melissa; Guo, Ruiting; Miller, Alex; Ribeil, Jean‐Antoine; Davidson, David; et al.
Abstract: lovo‐cel (bb1111; LentiGlobin for sickle cell disease [SCD]) gene therapy (GT) comprises autologous transplantation of hematopoietic stem and progenitor cells transduced with the BB305 lentiviral vector encoding a modified β‐globin gene (β A‐T87Q ) to produce anti‐sickling hemoglobin (HbA T87Q ). The efficacy and safety of lovo‐cel for SCD are being evaluated in the ongoing phase 1/2 HGB‐206 study (ClinicalTrials.gov : NCT02140554). The treatment process evolved over time, using learnings from outcomes in the initial patients to optimize lovo‐cel's benefit–risk profile. Following modest expression of HbA T87Q in the initial patients (Group A, n = 7), alterations were made to the treatment process for patients subsequently enrolled in Group B ( n = 2, patients B1 and B2), including improvements to cell collection and lovo‐cel manufacturing. After 6 months, median Group A peripheral blood vector copy number (≥0.08 c/dg) and HbA T87Q levels (≥0.46 g/dL) were inadequate for substantial clinical effect but stable and sustained over 5.5 years; both markedly improved in Group B (patient B1: ≥0.53 c/dg and ≥2.69 g/dL; patient B2: ≥2.14 c/dg and ≥6.40 g/dL, respectively) and generated improved biologic and clinical efficacy in Group B, including higher total hemoglobin and decreased hemolysis. The safety of the lovo‐cel for SCD treatment regimen largely reflected the known side effects of HSPC collection, busulfan conditioning regimen, and underlying SCD; acute myeloid leukemia was observed in two patients in Group A and deemed unlikely related to insertional oncogenesis. Changes made during development of the lovo‐cel treatment process were associated with improved outcomes and provide lessons for future SCD GT studies. Abstract : Treatment process evolution. *The target TNC for BMH was ≥6 × 10 8 /kg per patient. The Group B1 patient received lovo‐cel produced using both the original and refined manufacturing process, and the Group B2 patient received lovo‐cel produced using only the refined manufacturing process. Both Group B patients received lovo‐cel manufactured from HSPCs collected using BMH; however, the Group B2 patient also underwent rescue HSPC collection by plerixafor mobilization/apheresis for the exploratory evaluation of its safety and enhancement of the lovo‐cel manufacturing process. The Group B2 patient did not receive lovo‐cel manufactured from HSPCs collected using plerixafor mobilization/apheresis. Figure adapted from N Engl J Med, Kanter, J. et al., Biologic and Clinical Efficacy of LentiGlobin for Sickle Cell Disease, 386, 617‐628. Copyright © 2022 Massachusetts Medical Society. Reprinted with permission. AUC, area under the curve; BMH, bone marrow harvest; DP, drug product; HSPC, hematopoietic stem and progenitor cell; TNC, total nucleated cell count.